DISCIPLINE, WORK ENVIRONMENT, COMMITMENT, AND PERFORMANCE OF HEALTH WORKERS IN ENDE CITY DURING THE COVID-19 PANDEMIC: A PERCEPTIONAL STUDY - Mea, Maria Helena Carolinda Dua (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2023)
The purpose of this research is to investigate the effect of work discipline, work environment, and commitment on the success of health workers in Ende City during the Covid-19 pandemic. This is an observation study that is quantitative in nature. SmartPLS Software is used for data processing. There were 63 health professionals who responded. Multiple linear regression analysis was used with a sample size of 63 individuals. According to the t test findings, discipline and work environment have a significant and positive impact on performance, whereas commitment has no significant and negative impact. The R test findings of 0.567 show that discipline, commitment, and work environment variables influence the performance of health workers by 57%. While the remaining 43% is influenced by variables outside the scope of this study.